Legal Remedies for Notary Involvement in Land Mafia Cases (Case Study of Verdict Number 272/PID/2021/PT DKI) - Aldian Kukuh Trisetiyadi; Muhammad Sofyan Pulungan (LEGAL BRIEF, 2022)
Land is one of the valuable assets, because it has a high economic value. Land is a vital object in human life, because it has various values. Due to the high demand for land, it triggers the number of land mafias. The land mafia mode is to issue land evidence, manipulate cases and pretend to carry out land sales and purchase transactions. If someone wants to make a sale and purchase, someone is needed in the process of making the Sale and Purchase Deed. In the case of the land mafia that is currently rife, they will later work with a notary to process the AJB. The provisions of the Law on Notary Positions and this Code of Ethics have regulated the obligations and prohibitions of a Notary in carrying out his duties. The form of research used in this research is normative juridical research, namely research that refers to theories and laws and regulations related to this research. If there is a violation committed by a Notary which has been prohibited by laws and regulations. The notary will be subject to a code of ethics sanction as well as sanctions in the Notary Position Act. There are several efforts that can be done to eradicate the land mafia that is so rampant in Indonesia: 1) take firm action against the land mafia actors; 2) improve the integrity and professionalism of the apparatus; 3) improve cooperation/coordination between apparatus in handling and eradicating land mafia; 4) carry out land certification.